Economic analysis for ecosystem service assessments - Ian Bateman; Georgina Mace; Carlo Fezzi; Giles Atkinson; Kerry Turner (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
The paper seeks to contribute to the expanding literature on ecosystem service assessment by considering its integration with economic analyses of such services. Focussing upon analyses for future orientated policy and decision making, we initially consider a single period during which ecological stocks are maintained at sustainable levels. The flow of ecosystems services and their contribution to welfare bearing goods is considered and methods for valuing resultant benefits are reviewed and illustrated via a case study of land use change. We then broaden our time horizon to discuss the treatment of future costs and benefits. Finally we relax our sustainability assumption and consider economic approaches to the incorporation of depleting ecological assets with a particular focus upon stocks which exhibit thresholds below which restoration is compromised.
Keywords: 330; Ecosystem services; economic valuation; stocks and flows; wellbeing; spatial and temporal issues; sustainability; irreversibility; UK National Ecosystem Assessment (UK NEA); Umweltschutz; Umweltpolitik; Wohlfahrtseffekt; Bewertung; Großbritannien